Post-retirement re-socializing and adaptation challenges faced by sport elite: questionnaire survey - Fedotova, I. V.; Statsenko, M. E.; Tamozhnikova, I. S. (Theory and Practice of Physical Culture, 2019)
Modern elite athletes comprise a special social group that enjoys, on the peak of its competitive form, high social recognition and demonstrates high fortitude and willpower - and at the same time and for the same reasons is highly vulnerable in the post-retirement transitional period when the lifelong goals, standards and values appear no more relevant and new lifestyle needs to be built up from scratch on a totally different basis. The article analyzes the post-retirement re-socializing challenges faced by the sport elite in the first five years upon retirement from active trainings and competitions. We used a special questionnaire survey form to find the health and social problems faced by the elite athletes at that time. Sampled for the survey were 364 newly retired elite athletes whose re-socializing processes and challenges were tested by 102 case studies with a special attention to their health disorders and addictions (alcohol and tobacco); sleeping disorders; body weight growth; and the growing communication difficulties at work that may be considered predictors of the de-adaptive disorders in the physical and social health triggered by retirement from active sports. The mental and physical health disorders may evolve with time into serious antisocial issues in the post-retirement re-socializing process of the former sport elite.